El método Hervat: estrategia eficaz, para mejorar la atención en el sexto grado de Educación General Básica - Vargas Ochoa, María Fernanda (2023)
The present work entitled: The Hervat method: an effective strategy to improve attention in the sixth grade of General Basic Education has as general objective: To determine the influence of the Hervat method in the improvement of attention in the sixth grade "A" of General Basic Education, of "Miguel Riofrío" school; this research is descriptive, with mixed approach and quasi-experimental design; The scientific, statistical, synthetic, analytical and descriptive methods were used; likewise, to obtain the necessary information for the study, an interview with the teacher and the attention test were applied to the students; the population investigated corresponds to twenty-three students and a teacher of the sixth parallel grade "A". The results show that the students have a low level of attention and it is necessary to take actions aimed at improving it, therefore, the proposal "I relax and pay attention" was designed and implemented, which has as its main input the Hervat method; after its execution, the test was applied for the second time and the data shown in a comparative table with those of the first application show flattering results, demonstrating that the proposal was effective in raising the level of attention, motivation, memory, participation and academic performance of the students, as well as in reducing stress and anxiety. It is concluded that the Hervat method is effective in improving students' attention and therefore their academic performance and, subsequently, teachers are invited to consider the application of this method in their pedagogical practices in order to promote greater attention and interest on the part of the students. Keywords: Hervat method, memory, attention, school performance, motivation, educational strategies.